(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الهندسية, 2016)
اهتم الصناعيون بأتمتة مصانعهم لزيادة الانتاج وخفض التكاليف وتحسين جودة المنتج من خلال استخدام الأذرع الآلية في قيادة وانهاء معظم العمليات الانتاجية، حيث تتصف الأذرع الآلية بأنها هياكل ميكانيكية قابلة للبرمجة لأداء مهام تتميز بالدقة والسرعة والوثوقية. استند البحث في استنتاج المسار الأمثل على توليد مسارات افتراضية (مثلثية، منحنية، مربعة) تعبر عن حركة الذراع الآلي للوصول إلى نقطة الهدف، حيث تم معرفة زمن الانتقال وزوايا الدوران والعزم في المفاصل تحت تأثير الجاذبية الأرضية من خلال دراسة الحركة الأفقية والشاقولية للذراع الآلي. تبين حركة الذراع الآلي وفق المسارات المقترحة أن أفضل المسارات سلامة على محركات الذراع الآلي هو المسار النصف دائري كونه يحد من حدوث صدمات ميكانيكية أو ظهور قيم مرتفعة للعزوم عند المفاصل. في حين تبين ان المسار الذي يحقق أقل زمن للوصول الى نقطة الهدف وبالتالي اقل كمية في الطاقة المستهلة هو المسار المثلثي في حالة الحركة الافقية للذراع على الرغم من ظهور انحرافات حادة في مخططات العزم والطاقة نتيجة التغير المفاجئ في اتجاه الحركة. يظهر التأثير السلبي للجاذبية الأرضية خصوصا عند حركة المفصل الثاني للأعلى أو الأسفل, مما يسبب بظهور قمم في منحني الطاقة تعبر عن قيم مرتفعة للعزم في هذا المفصل. Industrialists interested automates their factories to increase production, reduce costs and improve quality by using robots in leadership and finishing most of the production processes, where robots characterized as mechanical structures programmable to perform tasks accurate, speed and reliability. Research depend in concluding the optimal path on generating virtual paths (triangular, curved, square) reflects the robotic arm movement to reach the target point, where as it has been known moving time and angles of rotation and torque in the joints under the influence of gravity through the study of horizontal and vertical movement of the robotic arm. A study of suggested trajectories for the robotic arm shows that the best paths on the safety of robotic arm motors is semi-circular path as limiting the occurrence of mechanical shocks or the appearance of high values of the joints torques. while showing that the path that achieves less time to reach the target point and less amount of energy is the triangular path in the case of horizontal motion of the robotic arm despite the emergence of sharp deviations in the torque and power schemas as a result of the sudden change in the direction of movement. The negative impact of gravity is especially apparent when the second joint up or down movement, causing the appearance of peaks in energy curve reflects the high values of determination in this joint.